Competency Improvement Through Digital Basic Skills Training for North Lampung Integrated Health Post Cadres in 2025 - Oktalia Liviyana; Tiara Amelia; Rohman Daka (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: The Ministry of Health's primary healthcare transformation emphasizes a promotive and preventive approach through strengthening Integrated Primary Service Posts (Posyandu) throughout the lifecycle. Posyandu cadres play a crucial role in implementing ILP, but still face competency challenges in delivering integrated services. Digital training is one innovation to efficiently increase cadre capacity. This study aims to analyze differences in Posyandu cadre competency in five Core Training Courses (MPI) before and after participating in digital training in North Lampung Regency in 2025. Methods: The study used a one-group pretest-posttest pre-experimental design through the Plataran Sehat Learning Management System (LMS). The sample size was determined using WHO software using a two-sided hypothesis test for a population mean. Bivariate analysis used the Wilcoxon Signed Rank Test. Results: The analysis showed a significant difference in the competency of Posyandu cadres in all five Core Training Courses (MPI 1–MPI 5) before and after the digital training (p < 0.05). Conclusions: The digital training on Basic Skills for Posyandu Cadres effectively improved cadre competency and needs to be maintained and developed to support the transformation of primary healthcare services.